Development of Physics Learning Tools Based on Contextual Teaching And Learning in a Remote Island Area - Ilyas Ilyas; An Nisaa Al Mu’min Liu (Universitas Muhammadiyah Makassar, 2019)
The research attempted to know the information on exam result Development of Physics learning tool for the students of eleven grade in Ende Island by using contextual teaching and learning in Fluid materials. It was viewed from the aspect of validity. Practicality and effectiveness. The kinds of research were development research that revers to ADDIE development model, analysis phase, design Development, implementation and evaluation. The Subject of the research was Physics learning device with approach learning model contextual teaching and learning to the students of Eleven Grade Ende Island Senior High School there are twenty nine students. Data collection was done in this research by using technique documentation. The data collection of research were done by using technique documentation, observations, survey and testing. The result showed that understanding the physics subject of fluid increased 82,7%, while students response showed positive response. This case showed that the reflection of the Egibilty of Development of Physics Learning tool based on Contextual Learning and teaching to increase the result of studying physic with Fluid materials.Keywords: Contextual Teaching and Learning, FluidaPenelitian ini bertujuan untuk mengetahui informasi hasil ujicoba perangkat pembelajaran fisika untuk peserta didik kelas X SMAN Pulau Ende dengan menggunakan model pembelajaran Contextual Teaching and Learning pada materi fluida ditinjau dari aspek kevalidan, kepraktisan dan keefektifan. Jenis penelitian ini adalah penelitian pengembangan yang mengacu model pengembangan ADDIE, dengan tahapan Analysis, Design, Development, Implementation, dan Evaluation. Subjek dalam penelitian ini adalah perangkat Pembelajaran fisika dengan pendekatan model pembelajran Contextual Teaching and Learning untuk peserta didik kelas XI SMAN Pulau Ende yang berjumlah 29 peserta didik. Pengumpulan data yang dilakukan dalam penelitian ini menggunakan teknik Dokumentasi, Observasi, dan Tes, Penyebaran Angket. Hasil penelitian menunjukkan bahwa pemahaman konsep fisika pokok bahasan fluida mengalami peningkatan 82,7%. Sedangkan respon siswa menunjukkan respon positif. Hal ini menunjukkan kelayakan pengembangan perangkat pembelajaran fisika Berbasis Contextual Teaching and Learning untuk meningkatkan hasil belajar fisika peserta didik materi fluidaKata kunci: Contextual Teaching and Learning, Fluida